Medical Instrumentation: Application and Design - John G. Webster [Editor] (Wiley India, 2004)
This premiere reference on medical instrumentation provides a comprehensive overview of the basic concepts of medical instrumentation showing the interdisciplinary nature of bioinstrumentation. It also features new material on infant apnea monitors, impedance pneumography, the design of cardiac pacemakers, and disposable defibrillator electrodes and their standards. · basic concepts of medical instrumentation · basic sensors and principles · amplifiers and signal processing · the origin of biopotentials · biopotential electrodes · biopotential amplifiers · blood pressure and sound · measurement of flow and volume of blood · measurements of the respiratory system · chemical biosensors · clinical laboratory instrumentation · medical imaging systems · therapeutic and prosthetic devices · electrical safety